A Model for a Structural Equation by Which to Evaluate the Relationships Between Students' Cultural and Economic Status and their Educational Achievement - Eduardo Hernández Padilla; Manuel Jorge González Montesinos (Universidad Autónoma de Baja California, 2011)
Because of its importance, socioeconomic status has been defined using different indicators, which establishes the benefit of separating the various effects that economic, social and cultural aspects have on students' learning. This study evaluates the different effects that economic, social and cultural factors have on scholastic achievement. The data analyzed come from the Quality and Scholastic Achievement Tests given to third-level preschool students (Excale-00) in the 2006-2007 school year. Through the modeling of structural equations, the theoretical relationships among a group of 15 indicators and three latent variables were analyzed, as well as each factor's contribution to scholastic achievement. Both factors have a positive association with learning, although the cultural factor has more influence than economic. The model suggested includes only a few indicators of both factors; further research should consider evaluating more indicators, and including other latent variables in the model.